Direct Evidence on Risk Attitudes and Migration - Jaeger, David A; Dohmen, Thomas; Falk, Armin; Huffman, David; Sunde, Uwe; Bonin, Holger (The Review of Economics and Statistics, 2010)
It has long been hypothesized that individuals' migration propensities depend on their risk attitudes, but the empirical evidence has been limited and indirect. We use newly available data from the German Socio-Economic Panel to measure directly the relationship between migration and risk attitudes. We find that individuals who are more willing to take risks are more likely to migrate. Our estimates are substantial compared to unconditional migration probabilities, as well the effects of conventional determinants of migration, and are robust to controlling for a variety of demographic characteristics. We find no evidence that our results are the result of reverse causality.